Genomic Analysis of Mycobacterium tuberculosis Strains Resistant to Second-Line Anti-Tuberculosis Drugs in Lusaka, Zambia - Joseph Yamweka Chizimu; Eddie Samuneti Solo; Precious Bwalya; Thoko Flav Kapalamula; Kaemba Kunkuta Mwale; David Squarre; Misheck Shawa; Patrick Lungu; David Atomanyi Barnes; Kaunda Yamba; Tiza Mufune; Herman Chambaro; et al. (MDPI AG, 2023)
The emergence of pre-extensively drug-resistant tuberculosis (pre-XDR-TB) is a threat to TB control programs in developing countries such as Zambia. Studies in Zambia have applied molecular techniques to understand drug-resistance-associated mutations, circulating lineages and transmission patterns of multi-drug-resistant (MDR) Mycobacterium tuberculosis. However, none has reported genotypes and mutations associated with pre-XDR TB. This study characterized 63 drug-resistant M. tuberculosis strains from the University Teaching Hospital between 2018 and 2019 using targeted gene sequencing and conveniently selected 50 strains for whole genome sequencing. Sixty strains had resistance mutations associated to MDR, one polyresistant, and two rifampicin resistant. Among MDR strains, seven percent (4/60) had mutations associated with pre-XDR-TB. While four, one and nine strains had mutations associated with ethionamide, para-amino-salicylic acid and streptomycin resistances, respectively. All 50 strains belonged to lineage 4 with the predominant sub-lineage 4.3.4.2.1 (38%). Three of four pre-XDR strains belonged to sub-lineage 4.3.4.2.1. Sub-lineage 4.3.4.2.1 strains were less clustered when compared to sub-lineages L4.9.1 and L4.3.4.1 based on single nucleotide polymorphism differences. The finding that resistances to second-line drugs have emerged among MDR-TB is a threat to TB control. Hence, the study recommends a strengthened routine drug susceptibility testing for second-line TB drugs to stop the progression of pre-XDR to XDR-TB and improve patient treatment outcomes.